2009
DOI: 10.1097/hjh.0b013e32831b46ab
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia alters renal cell responsiveness to pressure in a model of malignant hypertension

Abstract: Hyperglycemic environment alters responsiveness of renal cells to in-vitro simulation of malignant hypertension. The main consequence of either malignant hypertension or hyperglycemia is exaggerated apoptosis. However, the operating mechanisms differ: Malignant hypertension stimulates renal cell apoptosis via increased angiotensin-II, whereas hyperglycemia elicits apoptosis via augmented p53. By contrast to pressure-induced excessive proliferation of normoglycemic cells, hyperglycemia prohibits elevated prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The renal proximal tubular cell damage and apoptosis following the generation of ROS has been reported be responsible for the early stages of DN (3), and their sustained assault is believed to be critical in the progression of DN (34). The HG and ANG II seemed to be the key factors in the induction of intracellular ROS generation in the mitochondrial compartment, and that eventually leads to oxidative damage and apoptosis in renal cells (8,11,16,28). The p66Shc is a newly recognized mediator of mitochondrial dysfunction, which, by oxidizing Cyt.C in the mitochondria, leads to the generation of H 2 O 2 , and these sequence of events have been reported to be responsible for the pathogenesis of acute kidney injury in ischemia-reperfusion model (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The renal proximal tubular cell damage and apoptosis following the generation of ROS has been reported be responsible for the early stages of DN (3), and their sustained assault is believed to be critical in the progression of DN (34). The HG and ANG II seemed to be the key factors in the induction of intracellular ROS generation in the mitochondrial compartment, and that eventually leads to oxidative damage and apoptosis in renal cells (8,11,16,28). The p66Shc is a newly recognized mediator of mitochondrial dysfunction, which, by oxidizing Cyt.C in the mitochondria, leads to the generation of H 2 O 2 , and these sequence of events have been reported to be responsible for the pathogenesis of acute kidney injury in ischemia-reperfusion model (1).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increased expression of both total and p-p66Shc protein expression was seen in the HK-2 cells treated with HG or ANG II. The HG has been shown to increase the synthesis of ANG II (8) and expression of p53, a transcription factor. Interestingly, the consensus sequences for the binding of this transcription factor have been localized in the promoter region of p66Shc (19).…”
Section: Discussionmentioning
confidence: 99%
“…Five randomly chosen non-malignant cell cultures, namely human peripheral blood mononuclear cells (PBMC), human umbilical cord endothelial cells (HUVEC), rat renal epithelial cell (EC) line, murine renal mesangial cells (MC) and renal embryonic cells (REC) isolated from metanephric mesenchymal tissues, served as normal controls. All cells were sub-cultured and maintained using their specific selective media [12,13]. After 3 to 5 passages, each cell population was seeded into the wells of 6 well-tissue culture plates, 2x10 6 cells per well, using their specific culture media supplemented with fetal calf serum (FCS).…”
mentioning
confidence: 99%
“…Using an in vitro model of pressure-induced malignant hypertension, we have previously shown that mesangial cells play a deleterious role in orchestrating the acute renal tissue insult that is associated with malignant hypertension [1, 24, 25]. In this study, we focused on the podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The in-vitro model of malignant hypertension has allowed the investigation of paracrine crosstalk among various renal cell populations and their role in RAS activation in pressure-induced renal injury [1, 24, 25]. The first studies were performed on podocytes and mesangial cells firmly attached to culture vessels.…”
Section: Introductionmentioning
confidence: 99%